2005
DOI: 10.1248/cpb.53.1530
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Physicochemical Characterization of Microemulsion System Using Isopropyl Myristate, Medium-Chain Glyceride, Polysorbate 80 and Water

Abstract: Microemulsions are isotropic and thermodynamically stable dispersed micro-heterogeneous systems composed of water, oil and amphiphile.1) Their stability and unique solubilization properties have drawn attention for their use as vehicles for drug delivery. Microemulsions have the ability to protect labile drugs, control their release, increase their solubility and bioavailability and reduce patient variability. It has been proven possible to formulate preparations suitable for different routes of administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
3
15
0
2
Order By: Relevance
“…Accordingly, the nanocapsule size ranged from 224 to 264 nm for unloaded nanocapsules and from 233 to 276 nm for nanocarriers with encapsulated photosensitizer. The low and moderate values of the polydispersity index (PdI) determined for most of the microemulsions are in the range of 0.08-0.10 (Table I) and for obtained IR-loaded nanocapsules 0.10-0.13 (Table II) and characterize a reasonable monodispersity of the systems (33). All IR-780 loaded nanoparticles had a negative zeta potential ranging from -27.9 to -32.1.…”
Section: Resultsmentioning
confidence: 83%
“…Accordingly, the nanocapsule size ranged from 224 to 264 nm for unloaded nanocapsules and from 233 to 276 nm for nanocarriers with encapsulated photosensitizer. The low and moderate values of the polydispersity index (PdI) determined for most of the microemulsions are in the range of 0.08-0.10 (Table I) and for obtained IR-loaded nanocapsules 0.10-0.13 (Table II) and characterize a reasonable monodispersity of the systems (33). All IR-780 loaded nanoparticles had a negative zeta potential ranging from -27.9 to -32.1.…”
Section: Resultsmentioning
confidence: 83%
“…The solubility of ITTN was found to be highest in IPM (42.92 ± 3.97 mg/gm), a low molecular volume fatty acid ester and one of the most often used oils along with long chain triglycerides and medium chain triglycerides for ME (Subramanian et al 2005). It has been reported that the large solubilizing capacity of ME leads to larger concentration gradient toward the skin, providing superior dermal flux, for which high solubility of ITTN in oily phase can be an added advantage to increase it in ME.…”
Section: Development and Evaluation Of Microemulsionmentioning
confidence: 99%
“…Also, literature reveals that IPM acts as a chemical enhancer by disordering the prearranged lipids of the horny layer. To study the influence of oil on ME characteristics and penetration-enhancing ability, IPM was chosen for the preparation of MEcontaining ITTN (Patel et al 2009(Patel et al , 2011b(Patel et al , 2013aSubramanian et al 2005).…”
Section: Development and Evaluation Of Microemulsionmentioning
confidence: 99%
“…This is in line with previously published data. [31][32][33] The Tween 85 system displayed the characteristic swelling profile observed when the j of dispersed phase (water) is in- creased. The droplet size increased by 47% (w/w) to 3.5 nm as the j increased to 15% (w/w).…”
Section: )mentioning
confidence: 99%